(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to assess the local accounting procedures related in one of developments that have taken place, and largely on the structure of the Iraqi economic activity. But a partnership between the (public and private sector), or one of the types of joint arrangements, and through the use of the analytical method and extrapolate the reality of the accounting treatments in Company research sample. Research found to a number of conclusions that the unified accounting system applied in the economic units that deal with contracting joint arrangements formula suffers from obvious shortcomings, and reflected the common arrangements suffer from obvious shortcomings. and reflected on the quality of financial reporting, and the urgent need to adopt standards financial reporting (IFRS11)), to contribute to the promotion decisions related to joint arrangements as well as assessing the result of entering into such projects.